At the park - Ruttle, Kate (China, Oxford University Press, 2011)
At the Park explores sounds you might hear at the park and at a fun-fair. Dad takes the children and Floppy to the park on their bikes and scooters, they have a great time, but will he let them go on the fairground rides?